The Use of Communication Strategies in the Beginner EFL Classroom - Rodriguez, Carmen A.; Roux Rodríguez, Ruth (GIST – Education and Learning Research Journal, 2014)
When language learners do not know how to say a word in English, they can communicate effectively by using their hands, imitating sounds, inventing new words, or describing what they mean. These ways of communicating are communication strategies (CSs). EFL teachers are not always aware of the importance of teaching communication strategies to their students or, if they are aware, they do not explicitly train their students to use them. They do not use these strategies themselves to serve as a model to their students. Very often, what we have observed is that teachers abandon the message or switch to the first language to avoid communication problems in the classroom. This study investigated the communication strategies used by two EFL teachers and their beginner level students; and the potential factors that influence the communication strategies they use in class. Data came from three sources: (1) audio-recordings of naturally occurring classroom interactions; (2) interviews with the teachers; and (3) observation notes taken in six class sessions. Data from the interaction transcripts were examined using Faerch and Kasper’s (1983) taxonomy of communication strategies. Results indicated that the communication strategy most frequently used in both groups was language switch. However, while the teacher who seemed more involved with students used clarification request, comprehension check and asking for confirmation; the teacher who appeared more distant from students used comprehension check and repetition. Class size, seating arrangements and learning activity types were also some of the factors that influenced the communication strategies used.